Evaluating cognitive vigilance level between video game players and non-gamers after cognitive fatigue task / Muhammad Isamuddin Zani ... [et al.]. - Zani, Muhammad Isamuddin; Mohd Zaid, Amelia Natasya; Munshir Mohd Pozi, Muhammad Ariff; Zianuddin, Muhammad Haiqal; Mohd Nizam, Muhammad Hariz; Raja Hussain, Raja Nurul Jannat; Mohamed, Muhamad Noor (Universiti Teknologi MARA, Negeri Sembilan, 2025)
Video game players (VGPs) may exhibit unique cognitive advantages, including enhanced vigilance (1). However, the effects of cognitive fatigue on these abilities remain underexplored (2). The present study evaluates vigilance performance differences between gamers and non-gamers after a cognitively taxing task, addressing gaps in understanding the role of VGPs in mitigating cognitive fatigue while simultaneously aiming to clarify the potential of gaming in enhancing cognitive endurance.